Anti-ulcer Potential of Aqueous and Ethanolic Bark Extracts of â€œSaraca indicaâ€ Using Different Screening Models (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: Saraca indica (Cesalpiniaceae) is a plant, reported for its variety of ethnic medicinal uses, and widelygrown in Asia, Africa, and the Caribbean for its edible bark. The present work has been planned to screen the antiulceractivity of bark of the plant with the ethanolic and aqueous extracts. Materials and Methods: Bark powderwas successively extracted with ethanol (95%) and water using Soxhlet extraction and subjected to phytochemicalscreening to identify different phytoconstituents. Ld50 studies for both (ethanolic and aqueous) extracts wereconducted up to the dose level of 2 g/kg by following OECD up-and-down method of guidelines No.425. The antiarthriticactivity was performed using pylorus ligation, aspirin, and stress-induced ulcer models in rats. Statisticalanalysis was performed using one-way analysis of variance (ANOVA) followed by Dunnett’s test. P < 0.05 wasconsidered statistically significant. Results: Preliminary phytochemical studies revealed the presence of saponins,sterols, mucilage, glycosides, and alkaloids, steroidal saponins in both the ethanolic and aqueous extracts ofS. indica. No mortality was observed with aqueous and ethanolic extracts up to the maximum dose level of 2 g/kg.Both the extracts except with low dose 100 mg/kg other two doses, that is, medium and high have significantlyreduced the ulcer number (0.83 ± 0.0.16, 1.5 ± 0.34 and 0.50 ± 0.11, 0.66 ± 0.21), ulcer score (1.5 ± 0.12, 1.66± 0.16 and 0.83 ± 0.10, 0.91 ± 0.15), and ulcer index (13.64, 9.80 and 11.20, 8.25), and a significantly ulcerinhibition (41.10%, 27.30% and 68.76%, 54.25%) is noted. Conclusion: From the present experimental findingsof both pharmacological and biochemical parameters observed from the current investigation, it is concluded thatthe doses of 200 mg/kg and 400 mg/kg aqueous extract of S. indica possess potentially useful anti-ulcer activitysince it gives a positive result in ulcer score and ulcer index and a significant ulcer inhibition.